An observational study of the maintenance of the 30° side‐lying lateral tilt position among aged care residents at risk of developing pressure injuries when using the standard care pillow and a purpose‐designed positioning device. Issue 5 (12th July 2019) - Kapp, Suzanne; Gerdtz, Marie; Gefen, Amit; Prematunga, Roshani; Santamaria, Nick
Abstract: The aim of the study was to evaluate the maintenance of the 30° side‐lying lateral tilt position among aged care residents at the risk of developing pressure injuries when using the standard care pillow and a purpose‐designed positioning device. An observational study was conducted. Participants were monitored during positioning under two conditions, with pillows and with a fluidised positioner. Body angle measurements were taken at three time points (baseline, 1 hour, and 2 hours) on 10 occasions. Repeated‐measures analysis assessed the difference in the degree of the angle of the body. The sample (n = 12) had an average age of 83 years, and the participants were immobile when in bed. The average angle with the pillow condition was 26.7° at baseline, 21.5° at 1 hour, and 16.6° at 2 hours. The average angle with the fluidised positioner condition was 30.7° at baseline, 29.3° at 1 hour, and 26.8° at 2 hours. The main effects of Condition and Time were significant: Condition: F(1, 11) = 14.378, P  < .001, Time: F(2, 22) = 45.858, P  < .001. There was a statistically significant interaction between the effects of Condition and Time on the average lateral tilt position, F(2, 22) = 15.574, P  < .001. The lateral tilt body position was better maintained with the positioning device than the pillow. Further research is required to determine the effectiveness of the fluidised positioner for pressure injury prevention.